2015
DOI: 10.1103/physreva.91.013818
|View full text |Cite
|
Sign up to set email alerts
|

Quantum nonlinear optics near optomechanical instabilities

Abstract: Optomechanical systems provide a unique platform for observing quantum behavior of macroscopic objects. However, efforts towards realizing nonlinear behavior at the single photon level have been inhibited by the small size of the radiation pressure interaction. Here we show that it is not necessary to reach the single-photon strong-coupling regime in order to realize significant optomechanical nonlinearities. Instead, nonlinearities at the few quanta level can be achieved, even with weak-coupling, in a two-mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…To this end, several recent proposals have studied possible nonlinearities in optomechanical setups exploiting, for example, an enhanced optomechanical nonlinearity based on an optomechanical system employing a few optical modes * hseok@kongju.ac.kr [25][26][27][28], an intrinsic mechanical nonlinearity [29,30], and the coupling of mechanical systems to a qubit [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, several recent proposals have studied possible nonlinearities in optomechanical setups exploiting, for example, an enhanced optomechanical nonlinearity based on an optomechanical system employing a few optical modes * hseok@kongju.ac.kr [25][26][27][28], an intrinsic mechanical nonlinearity [29,30], and the coupling of mechanical systems to a qubit [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…(34). To keep the notation uncluttered, we will work out the results for a general Wigner-transformed propagators as a first step.…”
Section: Migdal-eliashberg Self-energy: the General Casementioning
confidence: 99%
“…For example, the same framework can be employed to study the recently observed enhancement of electron-phonon coupling in periodically distorted graphene [33] and driven opto-mechanical cavities [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced nonlinearity has been discussed in the context of detectors for phonons or photons [26], quantum memory [28], and to improve [27] the parameters of mechanically induced photon antibunching [29,30]. In the context of the phonon laser transition the enhanced optomechanical instability with two optical modes has been anticipated as a possible complication for gravitational wave detectors [31], and has been studied experimentally [11][12][13][14][15]32] and theoretically [33][34][35][36][37][38] in the classical regime.…”
Section: Introductionmentioning
confidence: 99%
“…However, the requirements to see phonon antibunching scale unfavorably with the system parameters, so that sub-Poissonian phonon statistics has eluded experimental observation. In this Rapid Communication we propose to make use of the enhanced optomechanical nonlinearity [25][26][27] of a setup with two optical modes to overcome this difficulty and prepare phonon laser states featuring antibunching in steady state with state of the art optomechanical crystals.…”
Section: Introductionmentioning
confidence: 99%